Interpreting the Concept of Ngalap Berkah as Pesantren Tradition in the Perspective of Santri - Syihabuddin, Muhammad; Manggala, Kayan; Wafi, Hasan Abdul; Maulana, Ahmad Harish (The Institute of Research and Service Community IPMAFA Pati, 2023)
Discussion on the tradition of Pesantren is critical and needs to be studied in more depth. This is because the study never ceases to be debated both from the historical side and its characteristics. This goal aims to understand three things: First, the existence of students viewed from the point of historicity through the study of the sociology of religion in Indonesia. Second, the paradigm of the concept of barakah is rooted in the world of Pesantren. Third, understanding the concept of barakah that internalizes students to take action in tabarruk or ngalap berkah social practices. The method used is through a literature study approach, examining the texts of articles with similar themes based on the theory of symbolic interactionism. Data collection is carried out by selection, classification, and categorization. The results found three things: First, in the study of the sociology of religion, Santri is an essential element in the Indonesian subculture called Pesantren. The existence of Santri is the typical determinant of a Pesantren. Second, the concept of barakah that students understand is very diverse; some call it ziyādatul khoīr, the Grace of God, miracles, benefits, and an amulet. In this case, the variety of meanings is adjusted to each insight and experience of Santri in Pesantren. Third, the concept of ngalap berkah becomes a tradition in Pesantren as a form of social practice of Santri which starts from the understanding of each Santri. The term tabarrukan is divided into two parts, namely in the form of ta’zīm and sam’an wa thā’atan. The conclusion of this paper shows that these three aspects (santri, barakah, and ngalap berkah) are a unity that cannot be validated in forming a pesantren.